Memoria Viva Responsabilità del ricordare e partecipazione civica - Menegatto, Marialuisa; ZAMPERINI, ADRIANO (Proceedings e report, 2015)
"Not forgetting" and "not remembering". These two contradictory aspects have always furrowed the autobiographical and collective memory of dramatic historical events, such as the Holocaust. This volume, whose origin lies in a couple of conferences held in Pistoia and Florence during the celebrations of the 2014 Day of Remembrance, moves along these two rough paths of remembrance. At its centre, there is Andrea Devoto's work on the memory of political deportation in Tuscany. The invited authors have tried to weave links and to signal new methods of analysis, as well as reflections, accompanied by the awareness that the keystone for the past lies in the present. For this reason, this book is intended to act as a dialogue partner within the social practices of the citizens' memory and civic training.